The Effect of Integrating Problem-Based Learning with Interactive Multimedia on Students’ Communication Skills in Pancasila Education - Fofi Fana; Andi Kristanto; Fajar Arianto; Shahrin bin Hashim (Institute of Multidisciplinary Research and Community Service, 2026)
Effective communication skills are essential competencies in 21st-century learning; however, students often demonstrate limited ability to express ideas, engage in discussions, and respond appropriately in classroom interactions. This issue highlights the need for innovative instructional approaches that actively involve students in meaningful learning processes. Therefore, this study aims to examine the effect of implementing the Problem-Based Learning (PBL) model supported by interactive multimedia on students’ communication skills. This study employed a quasi-experimental nonequivalent control group design. The participants consisted of 64 eleventh-grade students at SMA Negeri 9 Surabaya, divided into an experimental group (n = 32) and a control group (n = 32), selected through convenience sampling. Data were collected using a communication skills performance test administered as a pretest and posttest. The instrument was validated by experts to ensure content validity. Data analysis included normality and homogeneity tests, followed by an independent samples t-test to examine differences between groups. The results showed that the experimental group achieved a higher mean posttest score (M = 90.63) compared to the control group (M = 81.09). The independent samples t-test yielded a p-value of 0.000 (p 0.05), indicating a statistically significant difference between the two groups. In conclusion, the implementation of PBL supported by interactive multimedia has a significant positive effect on students’ communication skills. This approach promotes active engagement and meaningful learning, making it an effective strategy for improving communication skills in Pancasila Education. Keywords: PBL, Interactive Multimedia, Communication Skills